CONSUMER HEALTH INFORMATION: A BRIEF CRITIQUE ON INFORMATION NEEDS AND INFORMATION SEEKING BEHAVIOUR - Mustapha Khalil, Ferida Enolil (Malaysian Journal of Library and Information Science, 2001)
A brief analysis of information seeking by consumers regarding health information. The field of consumer health information is emerging slowly but surely, as consumers strive to understand diagnoses, maintain states of wellness, or even practising precautions to avoid known triggers of illnesses.